Preparasi Material Sensor Kreatinin dengan Metode Molecularly Imprinted Menggunakan Prekursor MBAA dan AMPSA - Karmanto, Karmanto; Muzani, Ahmad Amjad (Al-Kimia, 2018)
Synthesis and preparation of creatinine sensor material by molecularly imprinted method using N,N'-Methylenebisacrylamide (MBAA) and 2-Acrylamido-2-methyl-1-propanesulfonic acid (AMPSA) as precursors, on nylon membrane had been conducted. The precursor i.e. MBAA and AMPSA is used as cross-linker monomer, and functional monomer respectively, with the creatinine as template. The performance of creatinine sensor material been studied by instrument response (resistance) pattern analysis to concentration of creatinine. The result of FTIR spectra and SEM photograph, indicated the formation of molecularly imprinted polymer (MIP) on nylon membrane. Logarithmic pattern is appears as instrument response to concentration change of creatinine. Linear correlation of instrument response and creatinine concentration is observed at concentration ranges 1 to 5 ppm of creatinine. Comparative studies show that performance of nylon coated membrane is better than non-coated membrane. Linearity, limit detection, and limit quantification value of coated membrane is 0.9592; 1.2066 ppm; and 4.0221 ppm respectively. On the other hand for non-coated membrane, linearity, limit detection, and limit quantification value obtainedis 0.8799; 2.1607 ppm and 7.2044 ppm respectively.